Analysis of the Relation Between and Impact of Public Service Media and Private Media - Nielsen, R; Fletcher, R; Sehl, A; Levy, D (Reuters Institute for the Study of Journalism, 2016)
This consultation paper is prepared by the Reuters Institute for the Ministry of Culture (Denmark) and is based on examination of more than a thousand academic and stakeholder studies on the relation between, and impact of, public service media and private media. It presents a closer review focusing on the most relevant 36 academic publications and 16 industry publications. We find that: 1) There is a significant amount of research that assess the political impact of public service media. 2) There is less research on the social impact of public service media. 3) There is little research that assesses the market impact of public service media.